Diving behavior of humpback whales (Megaptera novaeangliae) throughout their migratory cycle in the Western South Atlantic Ocean - Silva, Érika Soares Coelho da (Universidade Federal de Juiz de Fora (UFJF), 2021)
Is poorly known how the diving behavior during the migratory cycle of humpback whales Megaptera novaeangliae is affected by environmental characteristics of their seasonal habitats and their social roles. In this study, archival Argos satellite tags were deployed off the coast of Brazil in 32 humpback whales from the South Western Atlantic Ocean. Tags reported data for ~44 days (max = 124 days) and 92,058 dives. Statistical analysis showed that average dive depth varied between habitats, being shallower in the breeding area (BA, 22.6 m), intermediate during the migration (MI, 30.26 m), and deeper in the feeding area (FA, 35.16 m). The dives classified as deep (>80 m), were more predominant during migration. At FA, dives during the night were shallower and shorter than those performed during the day, at BA dives made during the day were deeper than all other diel phases. We have not found clear differences in dive depth and duration between social classes. The moon phases had a clear effect within BA but not within MI and FA, being shallower at full moon. We also saw that the shapes (U, V, Square), showed differences in dive depth and among habitats. Our data provide the first novel insights into the dive behaviors of individuals from the same population throughout their migratory cycle, performing different diving behaviors, different patterns of social class, shapes, depth range, diel and moon phase. Moreover, these findings and the understanding diving patterns in its drivers have important implications for ecological modelling, conservation policies. É pouco conhecido como o comportamento de mergulho durante o ciclo migratório das baleias jubarte Megaptera novaeangliae é afetado por características ambientais de seus habitats sazonais e seus papéis sociais. Neste estudo, tags satelitais do sistema Argos foram implantadas na costa do Brasil em 32 baleias jubarte no sudoeste do Oceano Atlântico. Os tags relataram dados de ~ 44 dias (máx = 124 dias) e 92,058 mergulhos. A análise estatística mostrou que a ...